Microbial Alpha-Amylase Production: Progress, Challenges and Perspectives - Babak Elyasi Far; Yassin Ahmadi; Ahmad Yari Khosroshahi; Azita Dilmaghani (Tabriz University of Medical Sciences, 2020)
Alpha-amylase reputes for starch modification by breaking of 1-4 glycosidic bands and is widely applied in different industrial sectors. Microorganisms express unique alpha-amylases with thermostable and halotolerant characteristics dependent on the microorganism's intrinsic features. Likewise, genetic engineering methods are applied to produce enzymes with higher stability in contrast to wild types. As there are widespread application of α-amylase in industry, optimization methods like RSM are used to improve the production of the enzyme ex vivo. This study aimed to review the latest researches on the production improvement and stability of α-amylase.